THU0096 Patients with Nr-Axspa Show A Statistically Higher Disease Burden in Clinical Practice Compared with Patients with Radiographic Axial Spa. (10th June 2014) - Jacobsson, L.T.; Husmark, T.; Theander, E.; Henriksson, K.; Büsch, K.; Johansson, M.
Abstract : Background: The ASAS axial SpA classification criteria was published in 2009 but so far there has been limited research on axial SpA patients in clinical practice. There is no diagnose code for non-radiographic axial SpA (nr-axSpA) and it is unclear which diagnosis these patients receive in clinical practice. Characterization of nr-axSpA patients in clinical practice is lacking in comparison with radiographic axial SpA (rad-axSpA). Objectives: The aim of this study was to characterize patients with axial SpA in clinical practice and to investigate similarities/differences between radiographic and non-radiographic axial SpA. Methods: This is a prospective, cross-sectional, multi-center cohort study from Sweden. SpA patients (diagnosed with Psoriatic Spondylitis (M07.2), Ankylosing Spondylitis (M45), Spinal entesopathy (M46.0), Sacroiliitis, not elsewhere classified (M46.1), Other specified inflammatory spondylopathies (M46.8), or Inflammatory spondylopathy, unspecified (M46.9)) were consecutively recruited from the clinical settings of the participating study centers. Patients were followed for three months via an online questionnaire. At baseline, the rheumatologist assessed the ASAS axial SpA criteria and registered information on disease history, extra articular manifestations, and treatments. The patients answered online questionnaires capturing patient demographics, disease activity and function (BASDAI, BASFI, HAQ-S, etc.), QoL (EQ-5D, AS-QoL), health care resource use, and work ability (WPAI). P-values, unadjusted for covariates, were calculated using chi-square tests for categorical variables and t-tests for continuous variables. Results: 251 patients were included of whom 197 (78%) were classified as axial SpA. Of those, 125 (63%) were classified as rad-axSpA and 72 (37%) were classified as nr-axSpA according to the ASAS axial SpA criteria. The nr-axSpA patients were diagnosed with AS (35%), other specific inflammatory spondylopathies (31%), inflammatory spondylopathy unspecified (19%), psoriatic spondylitis (11%), and sacroilitis, not elsewhere classified (4%). Time between symptom onset and diagnosis was 9.0 (8.4) years for rad-axSpA and 6.7 (7.1) years for nr-axSpA. The nr-axSpA patients showed a higher disease burden compared with rad-axSpA patients, e.g. higher BASDAI (4.1 vs. 2.7), VAS global (4.3 vs. 2.9), VAS pain (4.4 vs. 2.9), and ASDAS (CRP) (2.3 vs. 1.9) (Table). Conclusions: In this study, from Swedish clinical practice, we included patients from rheumatology clinics with pre-specified diagnoses most likely to be classified as axial SpA. The results show that the nr-axSpA patients have a statistically higher burden of disease than patients with rad-axSpA. Acknowledgements: This study was sponsored by AbbVie. AbbVie contributed to the study design, research, and interpretation of data, writing, reviewing, and approving the publication. The authors determined the final content. No payments were made to the authors for writing this manuscript. Disclosure of Interest: : L. Jacobsson Consultant for: AbbVie, Pfizer, UCB, T. Husmark Consultant for: AbbVie, E. Theander Consultant for: AbbVie, K. Henriksson Consultant for: AbbVie, K. Büsch Shareholder of: AbbVie, Employee of: AbbVie, M. Johansson Employee of: AbbVie DOI: 10.1136/annrheumdis-2014-eular.2481